2020
DOI: 10.1093/tas/txaa109
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of six large-pen feedlot studies: effects of a noncoated initial and terminal implant compared with a single initial and delayed-release implant on arrival in feedlot heifers

Abstract: Abstract Randomized complete block design experiments (n = 6 experiments) evaluating steroidal implants (all from Merck Animal Health, Madison, NJ) were conducted in large-pen feedlot research facilities between 2015 and 2018 comparing an 80 mg trenbolone acetate (TBA) and 8 mg estradiol-17β (E2) initial implant (Revalor-IH) and re-implanted with 200 mg TBA and 20 mg E2 (Revalor-200; REPEATED) to a single 80 mg TBA and 8 mg E2 uncoated; 120 mg TBA and 12 mg E2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…Heifers saw an 8.9% response in ADG after implantation of ONE Grower over a 200-d feeding period which resulted in a 0.11 kg/d improvement in ADG. As evidenced in this study, the use of long-acting implants such as ONE Grower greatly improved final BW and ADG through 200 d. Although not researched in this study, with treatments commingled within pen, historical data utilizing implants suggest that use of ONE Grower for at least 200 d would likely increase DMI and gain efficiency compared to Control ( Smith et al, 2019a , 2020 ). This is further supported by the Synovex ONE Feedlot approval work which resulted in a 4.7 and 4.5% increase in DMI for steers and heifers, respectively, while seeing an 8.0% and a 7.0% increase in gain efficiency for steers and heifers, respectively ( Cleale et al, 2012 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Heifers saw an 8.9% response in ADG after implantation of ONE Grower over a 200-d feeding period which resulted in a 0.11 kg/d improvement in ADG. As evidenced in this study, the use of long-acting implants such as ONE Grower greatly improved final BW and ADG through 200 d. Although not researched in this study, with treatments commingled within pen, historical data utilizing implants suggest that use of ONE Grower for at least 200 d would likely increase DMI and gain efficiency compared to Control ( Smith et al, 2019a , 2020 ). This is further supported by the Synovex ONE Feedlot approval work which resulted in a 4.7 and 4.5% increase in DMI for steers and heifers, respectively, while seeing an 8.0% and a 7.0% increase in gain efficiency for steers and heifers, respectively ( Cleale et al, 2012 ).…”
Section: Discussionmentioning
confidence: 62%
“…Growth-promoting implants are a technology that provides a great improvement in feedlot cattle performance and a substantial return on investment to feedlot operators ( Duckett et al, 1996 ) which has resulted in over 90% of feedlot cattle being implanted at least once ( NAHMS, 2013 ) during the feedlot period. Cattle implanted with TBA and estradiol (either estradiol-17β [E 2 ] or EB) were shown to repeatedly improve ADG, DMI, and feed conversion while reducing marbling score and USDA yield grade ( Smith et al, 2019b , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was likely due to alterations of implant type on adipogenic gene expression [ 27 , 28 ], although this was not evaluated in the present study. Others have indicated that marbling is increased in heifers administered a single coated implant or an initial and terminal implant with a non-coated implant [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…As changes in carcass composition may be expected when comparing Revalor-XH to a more traditional re-implant program ( Smith et al, 2020 ), it may also be important to evaluate optimal days-on-feed (DOF) when using differing implant programs. Including a serial harvest treatment factor is a method for estimation of incremental dressing percentage (incremental carcass gain/incremental live gain), the estimated proportion of live weight gain that results in carcass weight gain ( Streeter et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%